Influence of hold type and duration on cyclic deformation behaviour of IN740H. Issue 4 (4th March 2019) - Singh, R. K.; Sahu, J. K.
ABSTRACT: The superimposition of time-dependent damage on fatigue, otherwise, known as creep-fatigue interaction (CFI), significantly affect the fatigue life of power plant boiler components. IN740H is a candidate material for advanced ultra-supercritical (A-USC) boilers components. The creep-fatigue interaction of alloy IN740H was studied at 760°C, by conducting low cycle fatigue (LCF) at a strain amplitude (Δ ϵt /2) value of 0.4% and holding at peak strain in tension, compression and both for 0, 1, 5, 10 and 30 min duration. Though hold time adversely affects fatigue life, tensile hold is the most damaging of all three hold modes. The reason behind maximum damage with tensile hold is grain boundary cavitations and coalescence of cavities leading to internal cracks formation at grain boundaries.